TINJAUAN YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 106/PUU-XVIII/2020 TENTANG PENGGUNAAN NARKOTIKA UNTUK KEBUTUHAN MEDIS - Muhammad Arif; Emilda Firdaus; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Whereas according to the Petitioners, the Elucidation of Article 6paragraph (1) letter a and Article 8 paragraph (1) of Law 35 of 2009 concerningNarcotics has resulted in the loss of the Petitioners' rights to obtain healthservices as stipulated in Article 28H paragraph (1) of the 1945 ConstitutionArticle 7 paragraph (1) Law Number 35 of 2009, Article 7 stipulates thatnarcotics can only be used for the benefit of health services and/or scientificdevelopment knowledge and technology. But in article 8 paragraph 1 of Lawnumber 35 of 2009.Regarding this research, it can be classified into the type of normativelegal research related to the Constitutional Court decision number 106/puu-xviii/2020. From the results of the research problem there are two main thingsthat can be concluded. First, there is a discrepancy or unconstitutionality becausethere is a difference in sound, so a review is needed. Because in Article 7 it isclear that for health it may be used by any group as long as it is still usedaccording to doctor's recommendations and according to Health Law number 36of 2009 concerning health.Second, the Constitutional Court should not at all close the loophole onthe use of Narcotics Category I, which not only cannabis can be used for thebenefit of health services. The Constitutional Court realizes that for the use ofNarcotics Category I for the benefit of health services it must be supported by thereadiness of facilities and infrastructure as well as supporting scientific evidence,so that the Government needs to start by conducting comprehensive studies andresearch.Key Words : Decision, Constitutional Court, Narcotics, Medical.